Electricity Consumption and Economic Development in Nigeria - Ogundipe, Adeyemi A.; Akinyemi, Opeyemi; Ogundipe, Oluwatomisin M. (International Journal of Energy Economics and Policy, 2016)
The study examines the relationship between electricity consumption and economic development using an extended neoclassical model for the period 1970-2013. The study incorporates the uniqueness of the Nigerian economy by controlling for the role of institutions, technology, emissions, and economic structure in the electricity consumption-development argument. The study adopted a cointegration analysis based on the Johansen and Juselius (1981) Maximum Likelihood approach and a vector error correction model. In order to ensure robustness, the study adopted the Wald Block Endogeneity causality test to ascertain the direction of causal relationship between electricity consumption and economic development. The study found an existence of long-run cointegration equation with electricity consumption inversely related to economic development. Likewise, the vector error correction model failed to reject the null hypothesis of non-convergence in the long-run. Finally, the study found evidence supporting unidirectional causal relationship running from economic development to electricity consumption. Keywords: Electricity Consumption, Economic Development, Cointegration, Causality JEL Classification: L94, O1, N17